The Emerging Scholars' Network Within MNRS: From Acorns to Oaks. (February 2020) - Hetland, Breanna; Lindroth, Heidi; Kamp, Kendra; Edmiston, Elizabeth; Wierenga, Kelly L.; Hardin, Heather K.; Gilmore-Bykovskyi, Andrea; Topp, Robert; Hershberger, Patricia E.; Madigan, Elizabeth
As the nursing faculty shortage persists, there is an urgent need to develop emerging nurse scholars into research leaders capable of advocating for the profession and expanding on the mission to improve health. To address this need, the Midwest Nursing Research Society (MNRS) commissioned a student task force that led to the development of the Emerging Scholars Network (ESN). The purpose of this article is to describe how the ESN was developed, integrated, and promoted within the MNRS to advance the overall mission and sustainability of the society. The establishment and success of the ESN is described using the Five Developmental Stages of Organization Evolution. These stages include the following: (a) Developing a Concept; (b) Launching a Start-Up; (c) Establishing Credibility; (d) Creating Sustainability; and (e) Road to Maturing and Legacy. Recommendations for continued development of the ESN are provided.